CFD modelling of particle size effect on stoker coalfired boilers combustion - Choiron, Moch. Agus (Eastern-European Journal of Enterprise Technologies, 2018)
In the previous study, CFD simulation had been developed to predict combustion characteristic on the Fluidized Bed Boiler and Pulverized Boiler. The high demand on coal used for stoker-fired boilers in Indonesia the power plants provide challenge due to low thermal efficiency problem. In this study, CFD simulation is observed to predict the temperature distribution, heat of reaction, CO and CO2 mass fraction on the stoker-fired boiler. Boiler geometry is modelled as the combustion chamber until the area before economizer. The selection of boundary conditions is set according to the governing equations available in the ANSYS Fluent software. Parameter design of coal which are particle size and properties of coal is determined to investigate the effect of the observed values. Four models are set to provide a combination of particle size and properties of coal. The solution strategy is developed to reduce instability of the simulation process. Coal combustion modelling includes several physical processes that could result in numerical stability issue when all processes are solved at once. The three stages were used to run the solution of the model. Plot of temperature distribution, heat of reaction, CO2 and CO mass fraction is generated. The maximum temperature in the 1st to 4th model is 1440.95, 1473.85, 1347.72 and 1617.17 [oK]. The amount of CO produced from each model tends to increase; respectively from the 1st to 4th model is 2.314E-07, 5.878E-07, 5.678E-07 and 7.904E-07. Based on the simulation results, it can be seen that the particle size of coal affects the combustion characteristic in the Stoker Coal-Fire Boiler.